22 years of Minimal Incision Vertical Endoscopic Lift: a journey in endoscopic facial rejuvenation - Gennai, Alessandro; Colli, Mattia; Gaggio, Leonardo (Frontiers in Surgery, 2025)
IntroductionThe Minimal Incision Vertical Endoscopic Lifting (MIVEL) is a minimally invasive facial rejuvenation technique that repositions tissues with minimal scarring, reduced recovery time, and long-lasting results, while achieving a natural appearance. This study aims to describe the updated MIVEL procedure, focusing on its evolution over 22 years and providing methodological details. This includes refining the indications, identifying key fixation points for reproducible results, and highlighting the long-term success of MIVEL as an effective approach for facial rejuvenation with minimal scarring and reduced complications.MethodsThis retrospective analysis encompasses a comprehensive review of 784 patients who underwent MIVEL between 2001 and 2023. The MIVEL technique involves small incisions, endoscopic guidance, and vertical lifting to reposition facial tissues. Preoperative and postoperative photographs, patients' demographic data, and complication rates were analyzed. Included patients were those seeking facial rejuvenation without extensive skin excision and attending all follow-up visits up to at least one year postoperatively. Patients were categorized into three MIVEL groups (I, II, III) of dissection, based on their age and related aging signs.ResultsThe average age of patients was 50.5 years, with the majority falling in the MIVEL II group (53.1 years). MIVEL I was primarily performed on younger patients (21–35 years), while MIVEL III was reserved for those over 55 years. Adjunctive procedures, such as guided Superficial Enhanced Fat Fluid Injection (SEFFI), blepharoplasty, and neck lift, were commonly combined with the MIVEL procedure. The complication rates were low, with transient issues like neuropraxia and periocular ecchymosis being the most common. No cases of severe complications like skin necrosis or permanent nerve injury were reported.DiscussionMIVEL has proven to be a highly effective and well-tolerated technique for the rejuvenation of the upper and middle thirds of the face. Its minimally invasive nature reduces recovery times and minimal scarring while providing lasting and natural-looking results. The 22-year experience underscores the reliability and high patient satisfaction associated with MIVEL, making it a preferred choice for facial rejuvenation surgery. Future directions include further refining the technique and exploring its applicability to other facial and neck rejuvenation areas.